Sup35p in Its Soluble and Prion States Is Packaged inside Extracellular Vesicles - Mehdi Kabani (American Society for Microbiology, 2015)
ABSTRACT The yeast Saccharomyces cerevisiae harbors several prions that constitute powerful models to investigate the mechanisms of epigenetic structural inheritance. [PSI+] is undoubtedly the best-known yeast prion and results from the conversion of the translation termination factor Sup35p into self-perpetuating protein aggregates. Structurally different conformers of Sup35p aggregates can lead to [PSI+] strains with weak or strong prion phenotypes. Yeast prions are faithfully transmitted from mother to daughter cells during cell division, upon cytoplasmic mixing during mating, or when Sup35p fibrils made in test tubes are introduced into spheroplasts. Virtually all living cells in the three domains of life, Bacteria, Archaea, and Eukarya, secrete small membrane vesicles in the extracellular space. These extracellular vesicles (EV) have gained increasing interest as vehicles for the intercellular transfer of signaling molecules, nucleic acids, and pathogenic factors, as well as prion-like protein aggregates associated with neurodegenerative diseases. To begin to explore the question of whether EV could represent a natural mean for yeast prion transmission from cell to cell, we purified these extracellular vesicles and assessed whether they contained Sup35p. Here, we show that Sup35p is secreted within EV released in the extracellular medium of yeast cultures. We demonstrate that Sup35p within EV isolated from strong and weak [PSI+] cells is in an infectious prion conformation. Among the possible implications of our work is the possibility of previously unsuspected EV-mediated horizontal cell-to-cell transfer of fungal prions. IMPORTANCE Most living cells in the three domains of life, Bacteria, Archaea, and Eukarya, secrete small membrane vesicles in the extracellular space. These extracellular vesicles (EV) were long viewed as “trash cans” by which cells disposed of unwanted macromolecules. EV gained renewed interest as their roles as vehicles for the cell-to-cell transfer of nucleic acids, signaling molecules, and pathogenic factors were recently uncovered. Of particular interest is their proposed role in the prion-like propagation of toxic protein aggregates in neurodegenerative diseases. Yeasts naturally harbor prion proteins that are excellent models to investigate the mechanisms of formation, propagation, and elimination of self-perpetuating protein aggregates. Here we show for the first time that a yeast prion is secreted within EV in its infectious aggregated state. A major implication of our work is the possibility of EV-mediated horizontal spread of fungal prions.